Analysis of Affixation Errors Formal Spoken Language in Rakyat Bersuara Program September 2024 on Official iNews YouTube Channel: Analisis Kesalahan Afiksasi Ragam Baku Lisan dalam Acara Rakyat Bersuara Bulan September Tahun 2024 pada Kanal YouTube Official iNews - Nur Selvi Rasny; Abdul Malik; Legi Elfitra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The research aims to describe the types of affixation errors formal spoken language in Rakyat Bersuara program during September 2024 which were uploaded on Official iNews YouTube channel. This Research is descriptive research using a qualitative approach. The object of this research is Rakyat Bersuara program during September 2024. This research employs a documentation technique supported by listening and note-taking techniques as its data collection methods. The data analysis techniques used in this research are data reduction, data presentation, and verification. The result of this research revealed that there were several types of affixation errors formal spoken language in Rakyat Bersuara program during September 2024, which were categorized as follows. 1) sounds that should have undergone phonetic changes did not experience changes, as in word form memposisikan, mensejahterakan, mempolopori, and mengkonfirmasi. These errors indicate non-compliance with the lenition rules for phonemes /p, s, dan k/ in the prefix meN-; 2) improper morpheme abbreviation, as in word form nyapres, ngerasain, ngelarang, and ngelaporin. These errors occur due to morpheme simplications that do not align with the standard rules of the Indonesian language; 3) incorrect affix usage, as in word form ketemu, kepancing, korelisasi, meuji, maksimalisasi, bekatakan, kebayang, and ketangkap. These errors result from improper affix usage causing shifts in meaning and the formation of non-standard words; and 4) improper determination of root words, as in word form memeningkatkan, rohaniawan, mengkesampingkan, penggeroyokan, berkesesuaian, menggendarai, and dikesampingkan. These errors involves the use of affixes that change the form of the basic word which is not in accordance with linguistic rules.